Efficacy of crystallization test for screening of oral squamous cell carcinoma with clinico-pathological correlation - Sachin C Sarode; Gargi S Sarode; Suresh Barpande; Jagdish V Tupkari (Wolters Kluwer Medknow Publications, 2013)
Aim: To determine the efficacy of crystallization test for screening oral squamous cell carcinoma (OSCC) with clinico-pathologic correlation. Materials and Methods: Fifty patients of OSCC and 30 healthy individuals were selected. One drop of blood was collected into 1 cc of doubled distilled water at room temperature to give a final dilution of 6% hemolyzed blood. 0.1 to 0.2 cc of blood sample was then subjected to crystallization test using 10% cupric chloride solution. Results: In healthy control group, the typical pattern was an eccentrically placed center of gravity with needles arranged in radiating fashion, while in OSCC group, there was 'transverse form' (TF) formation. The sensitivity and specificity of this test was found to be 96% and 96.66%, respectively. The positive and negative predictive values were found to be 97.96% and 98.55%, respectively. The mean TF frequency was found to be increasing from grade I (3.20 ± 1.5%) to grade II (653 ± 2.23%) and difference was statistically significant (P = 0.0001). However, there was no correlation between mean TF frequency and TNM stages of OSCC. Conclusion: Crystallization test is a simple, reliable, economical, less time-consuming, and less invasive screening procedure, which can be used for early detection of OSCC.